Diabetes Mellitus among new tuberculosis patients in Bamako, Mali. (December 2019) - Diarra, B.; Tolofoudie, M.; Sarro, Y.S.; Togo, A.C.G.; Bane, S.; Nientao, I.; Cisse, A.B.; Kone, M.; Somboro, A.; Degoga, B.; Diallo, F.; Coulibaly, G.; et al.
Abstract: Introduction: Diabetes Mellitus (DM) increases worldwide, mostly in low- and middle-income countries. In Mali, the prevalence in the adult population is estimated at 1.8%, but tuberculosis (TB) patients are not systematically screened. The goal of our study was to determine the prevalence of DM among newly diagnosed TB patients. Methods: We conducted a cross sectional study and a pilot prospective cohort study in four health centers in Bamako. All patients underwent fasting capillary-blood glucose (FCBG) test at Day 0, and repeated after one-week of TB treatment. Venous FBG test was performed for discrepancies between the two FCBG results. Thereafter, FCBG was performed for pilot study at month-2 (M2) and M5 of TB treatment. Results: Two hundred and one patients were enrolled in this study. Impaired fasting blood glucose was identified in 17 (8.5%), of whom 11 (5.5%) had DM (VFBG >7 mmol/L). Among patients with DM, seven (63.6%) had successful TB treatment outcome, versus 142 (74.7%) of those without DM ( p  = 0.64), and (OR: 1.69, 95%CI 0.47–6.02). Conclusion: The prevalence of DM among TB patients in Bamako exceeds that of the general population and screening at TB diagnosis suffices to identify those with DM. Systematic screening of both diseases will allow better treatment.